Bioaccumulation of lead and non-specific immune responses in white shrimp (Litopenaeus vannamei) to Pb exposure. Issue 62 (March 2017) - Wu, Yu-Sheng; Huang, Shih-Ling; Chung, Hsin-Chieh; Nan, Fan-Hua
Abstract: In this study, we investigated organ accumulation and nonspecific immune response in white shrimp ( Litopenaeus vannamei ) that were exposed to various concentrations of lead (Pb) solution. The concentrations of Pb in the hepatopancreas, haemolymph, and muscle were measured moreover the total heamocyte count, phenoloxidase activity, O2 − and physiological factors such as glutamic oxaloacetate transaminase (GOT), glutamic pyruvic transaminase (GPT), and haemolymph glucose were detected. The results showed that the hepatopancreas was the main organ of accumulation of Pb in white shrimp and the cumulative concentration of each organ was positively correlated with the experimental Pb concentration and immersion time. By observing GOT and GPT, Pb was found to inhibit phenoloxidase and O2 − activity and to induce organ injury. Thus, the heavy metal Pb accumulates in the hepatopancreas and haemolymph and affects the crustacean metabolic organ injury (rising of GOT and GPT) further to inhibit nonspecific immune responses. Highlights: Hepatopancreas was the main organ accumulated heavy metals in the white shrimp. The accumulation concentration of Pb in the haemolymph was lower than in the hepatopancreas but greater than in the muscle tissue. Treating white shrimp with Pb solution, Pb inhibit the phenoloxidase activity and O2 − production. Treating with Pb, white shrimp was with an increased GOT, GPT enzyme, and glucose concentration was observed in the haemolymph.